A new A-site-deficient Ti-doped SrCoO3-δ perovskite cathode material for intermediate-temperature solid oxide fuel cells. Issue 1 (April 2019) - Tong, Ling; Tian, Dong
Abstract: To lower the operating temperatures of solid oxide fuel cells (SOFCs), A new A-site-deficient Ti-doped SrCoO3-δ (SCT) are synthesized by a modified Pechini method and used as new highly active and stable cathode materials for intermediate-temperature SOFCs. The phase structure and electrical, thermal, and electrochemical properties of the SCT samples are evaluated. A phase transformation of SrCoO3-δ from hexagonal to cubic perovskite structure occurred at room temperature by the substitution of Ti. A lower TEC value of the SCT oxide was observed with increasing the Ti doped content and A-site deficiency. NiO-SDC-supported single cells with various SCT as cathode materials were operated at intermediate temperatures using humidified H2 as fuel and the static air as oxidant, respectively. Significant improved electrochemical performance for the A-site-deficient SCT sample was observed. An open-circuit potential of 0.83 V and the max power density of 745 mW cm-2 were achieved at 650 °C. The experimental results indicated that the A-site-deficient Sr0.95Co0.9Ti0.1O3-δ cubic perovskites are promising candidates as cathode materials for IT-SOFCs.